2021
DOI: 10.1002/advs.202003404
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase 2 Mediates Alcohol‐Induced Colorectal Cancer Immune Escape through Stabilizing PD‐L1 Expression

Abstract: Despite the great success of immunotherapy in a small subset of cancer patients, most colorectal cancer (CRC) patients do not respond to programmed cell death receptor 1 (PD-1) blockade immunotherapy. There is an urgent medical need to elucidate how cancer cells evade immune response and to develop novel means to boost the efficacy of immune checkpoint inhibitors. In this study, alcohol induces ligand programmed cell death receptor 1 (PD-L1) expression of CRC cells in vitro and in vivo. Alcohol exposure is sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…Alcohol consumption induces ALDH2 and subsequently upregulates PD-L1 expression in CRC, thereby protecting it from immune surveillance. Therefore, the combination of ALDH2 inhibition and anti-PD-1 therapy enhances the anti-tumor immunity and can be used as a novel strategy to enhance the efficacy of ICB in CRC patients, especially those who consume alcohol [ 216 ].…”
Section: Advances In Pd-1/pd-l1 Blockade-based Combination Treatment ...mentioning
confidence: 99%
“…Alcohol consumption induces ALDH2 and subsequently upregulates PD-L1 expression in CRC, thereby protecting it from immune surveillance. Therefore, the combination of ALDH2 inhibition and anti-PD-1 therapy enhances the anti-tumor immunity and can be used as a novel strategy to enhance the efficacy of ICB in CRC patients, especially those who consume alcohol [ 216 ].…”
Section: Advances In Pd-1/pd-l1 Blockade-based Combination Treatment ...mentioning
confidence: 99%
“…ALDH2 is an enzyme involved in ethanol metabolism and acetaldehyde breakdown, such as 4‐hydroxykingenal and malondialdehyde, to acetate. In recent years, multiple studies have demonstrated pro‐colorectal cancer consequences of ALDH2 activation, which directly regulates metabolic and inflammatory responses 34 . The carnitine palmitoyl transferase system (CPTs) regulates fatty acid β‐oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, multiple studies have demonstrated pro-colorectal cancer consequences of ALDH2 activation, which directly regulates metabolic and inflammatory responses. 34 The carnitine palmitoyl transferase system (CPTs) regulates fatty acid βoxidation. In the outer mitochondrial membrane, CPT1 is situated, while CPT2 is located in the inner mitochondrial membrane.…”
Section: Rectummentioning
confidence: 99%
“… 63 Moreover, ALDH2 is linked to autophagy regulation in some diseases, and it was speculated that autophagy is one of the mechanisms that ALDH2 uses to regulate tumor occurrence and development. 64 , 65 In addition, ALDH2 indirectly regulates the immune system due to its role in aldehydes metabolism and acetaldehyde adducts, 66 , 67 and it may also be one of the mechanisms by which ALDH2 is involved in tumor development.…”
Section: Discussionmentioning
confidence: 99%